2011
DOI: 10.1007/s12603-011-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and health care costs for the elderly living in municipal residential homes - An intervention study

Abstract: With improved knowledge the staff could offer the elderly more individualised meals. One of their future challenges is to recognise and assess nutritional status among this group. If malnutrition could be prevented health care costs should be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
3
38
0
1
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38] Although relatively more studies were identified in this category, the studies were very diverse in terms of setting, interventions, and outcomes measured, making any direct comparisons across studies very difficult. In terms of study design, a range of designs were employed including randomised designs, [29][30][31]35 a number of non or quasi-randomised designs 32,33,36,37 and modelled studies. 34,38 Although sample size varied from less than 100 to over 2000, half of the studies included between 100 and 300 participants.…”
Section: Results Of Studies Where Participants Were Defined As Malnoumentioning
confidence: 99%
See 2 more Smart Citations
“…[29][30][31][32][33][34][35][36][37][38] Although relatively more studies were identified in this category, the studies were very diverse in terms of setting, interventions, and outcomes measured, making any direct comparisons across studies very difficult. In terms of study design, a range of designs were employed including randomised designs, [29][30][31]35 a number of non or quasi-randomised designs 32,33,36,37 and modelled studies. 34,38 Although sample size varied from less than 100 to over 2000, half of the studies included between 100 and 300 participants.…”
Section: Results Of Studies Where Participants Were Defined As Malnoumentioning
confidence: 99%
“…In addition, the costs included in the analysis varied from the incremental costs of providing the intervention only, [30][31][32] compared to wider viewpoints including the costs of providing the intervention and medical treatment over the follow up time period. 29,[33][34][35][36][37] One study focused on the changes in hospitalisation costs only. 38 Overall, while the heterogeneity of the studies makes synthesis of the outcomes difficult, they have generally indicated beneficial outcomes for the patient or health system, at a relatively low cost.…”
Section: Results Of Studies Where Participants Were Defined As Malnoumentioning
confidence: 99%
See 1 more Smart Citation
“…Five of these intervention studies were quasi-experimental with a comparison group (45,56,57,61,83) while another five were a single group with a pretest-posttest design (40,53,(84)(85)(86). The final study had a posttest design and involved qualitative observations at seven sites that received the intervention (62).…”
Section: Staff Training and Support For Mealtime Activitiesmentioning
confidence: 99%
“…The final study had a posttest design and involved qualitative observations at seven sites that received the intervention (62). The comparison group quasi-experimental studies originated from France (56), United States (83), and Sweden (45,57,61). Charras investigated a training program implemented in one LTC facility (n ¼ 8) versus another facility with no training program put in place (n ¼ 10) (56).…”
Section: Staff Training and Support For Mealtime Activitiesmentioning
confidence: 99%